PENGARUH TEKNIK ASERTIVE TRAINING DALAM MENGEMBANGKAN KONSEP DIRI POSITIF PADA SISWA SMP - Muhammad Musafir; Bela Janare Putra (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2022)
The purpose of this study was to examine the effect of developing a positive self-concept on students at SMP Negeri 4 Satu Atap Batauga. This type of research is a pre-experimental research. Pre-experiment is an arrangement of research designs carried out by giving treatment to subjects without a control group. Therefore, the form of pre-experimental design used is one group pre-test and post-test design. Based on inferential statistical analysis using the Wilcoxon test, it was obtained that P value = 0.013 and then consulted with the value of at a significance level of 5%. Pvalue (0.013 0.05) This means that H0 is rejected. Thus it can be concluded that group counseling services with Assertive Training techniques can develop a positive self-concept in class VIII students of SMP Negeri 4 Satu Atap Batauga.Keywords : Assertive Training Techniques, Positive Self-Concept, Junior High School Students